Does locating pets qualify as processing of personal data? - Vilponen, Pauliina (fi=Turun yliopisto|en=University of Turku|, 2018)
One noteworthy and unconventional form of data processing is accessing location information on an electronic collar worn by a pet. Technically, this kind of data collection is conducted within a mobile application operated on a mobile device. The collected location data closely connects to the location of the pet owner or another individual residing close to the pet. Therefore, the app developer operating the mobile application must comply with all relevant data protection legislation. The first part of this thesis explains, why a pet’s location qualifies as personal data, how this information is technically accessed, and which legal instruments regulate the use of this data. In addition, the first part addresses how the basic data protection principles and the obligation to acquire an individual’s consent create limitations regarding the use of the collected data. Furthermore, it is argued in the second part of this thesis that the real value of personal data to an enterprise is connected to the possibilities of third party data disclosure. In addition, it is argued that the European data protection rights, specifically the right to be forgotten and the right to data portability, significantly limit the app developer’s potential to economically benefit from the collected location data. In this regard, the second part also includes forming a model to transfer location data in a private corporate acquisition process. The main research method used in this thesis is problem-oriented legal dogmatics and the main legal context is the European data protection framework. The findings of this research are divided into two distinct arguments. Firstly, it is concluded that while rendering the collection of pets’ location data lawful, the app developer should not over-value an end user’s consent by considering it the sole sufficient basis to protect the fundamental rights and freedoms of the individual. Secondly, in the modern personal data economy, the app developer should treat personal information as a hybrid legal concept which effectively adapts itself to changing data protection situations. By including the end users to the data collection operations, the app developer also